Anticancer potential of AgNPs synthesized using acinetobacter sp. and curcuma aromatica against HeLa cell lines: a comparative study - Nadhe, Shradhda B.; Tawre, Madhumita S.; Agrawal, Sonia; Chopade, Balu A.; Sarkar, Dhiman; Pardesi, Karishma (Journal of Trace Elements in Medicine and Biology, 2020)
Background: Biogenic nanoparticles are gaining attention due to their low toxicity and numerous biomedical applications. Present study aimed to compare the potential anticancer activity of two biogenic silver nanoparticles (bAgNPs and pAgNPs) against human cervical cancer cell lines (HeLa). Methods: bAgNPs were synthesized using Acinetobacter sp. whereas pAgNPs were synthesized using aqueous root extract of Curcuma aromatica. Effect of these nanoparticles on HeLa cells viability was studied using MTT assay and colony formation assay. Anticancer potential was determined using fluorescence microscopy and flow cytometry studies. Bio-compatibility studies were performed against peripheral blood mononuclear cells (PBMCs). Results: Both the nanoparticles showed 50 % viability of peripheral blood mononuclear cells (PBMCs) when used at high concentration (200 mu g/mL). IC50 for bAgNPs and pAgNPs against HeLa cells were 17.4 and 14 mu g/mL respectively. Colony formation ability of Hela cells was reduced on treatment with both nanoparticles. Acridine orange and ethidium bromide staining demonstrated that bAgNPs were cytostatic whereas pAgNPs were apoptotic. JC-1 dye staining revealed that the mitochondrial membrane potential was affected on treatment with pAgNPs while it remained unchanged on bAgNPs treatment. Flow cytometry confirmed cell cycle arrest in HeLa cells on treatment with nanoparticles further leading to apoptosis in case of pAgNPs. About 77 and 58 % HeLa cells were found in subG1 phase on treatment with bAgNPs and pAgNPs respectively. bAgNPs showed cytostatic effect on HeLa cells arresting the cell growth in subG1 phase, whereas, pAgNPs triggered death of HeLa cells through mitochondrial membrane potential impairment and apoptosis. Conclusion: Overall, bAgNPs and pAgNPs could be safe and showed potential to be used as anticancer nanoantibiotics against human cervical cancer cells.
Keywords: Acinetobacter sp.; AgNPs; Anticancer; Curcuma aromatica; HeLa cells; PBMCs